Superiority of endoscopic interventions over minimally invasive surgery for infected necrotizing pancreatitis: meta‐analysis of randomized trials. Issue 3 (1st August 2019) - Bang, Ji Young; Wilcox, Charles Melbern; Arnoletti, Juan Pablo; Varadarajulu, Shyam
Abstract : Background and Aim: Infected necrotizing pancreatitis is a highly morbid disease managed by minimally invasive surgical (MIS) or endoscopy‐based interventions. This meta‐analysis compared the clinical outcomes of patients treated using either approach. Methods: MEDLINE and EMBASE databases were searched to identify all randomized trials that compared MIS and endoscopy‐based interventions for treatment of infected necrotizing pancreatitis. Main outcome measure was to compare rates of complications or death during 6‐month follow‐up. Results: Three studies involving 184 patients met inclusion criteria. While there was no significant difference in mortality (14.5% vs. 16.1%, risk ratio [RR] = 1.02, P = 0.963), new onset multiple organ failure (5.2% vs. 19.7%, RR = 0.34, P = 0.045), enterocutaneous fistula/perforation (3.6% vs. 17.9%, RR = 0.34, P = 0.034) and pancreatic fistula (4.2% vs. 38.2%, RR = 0.13, P < 0.001) were significantly lower for endoscopic interventions compared to MIS. There was no significant difference in intraabdominal bleeding, endocrine or exocrine pancreatic insufficiency between cohorts. Length of hospital stay was significantly shorter for endoscopy (standardized mean difference, −0.41, P = 0.010). Conclusions: An endoscopy‐based treatment approach, as compared to minimally invasive surgery, significantly reduces complications in patients with infected necrotizing pancreatitis.